2007
DOI: 10.1364/ol.32.001123
|View full text |Cite
|
Sign up to set email alerts
|

Cavity-dumped intracavity-frequency-doubled Yb:YAG thin disk laser with 100 W average power

Abstract: We report on a cavity-dumped Yb:YAG thin disk laser with intracavity-frequency doubling to provide pulses in the millijoule energy range at a repetition rate of up to 100 kHz. The maximum average output power at 515 nm was 102 W with pulses of a pulse length of 300 ns. An additional advantage of the presented laser setup is the wide tunability of the pulse duration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 4 publications
0
9
0
Order By: Relevance
“…Stolzenburg et al have shown a cavity-dumped thin-disk laser at more than 100 W output power, 300 ns pulse duration at repetition rates up to 100 kHz. 10 Fiber lasers are very capable devices that have advantages on thermal lensing compared to bulk lasers and can produce high power and high pulse energy. 11,12 As Alvarez et al have shown, ns fiber systems can deliver 2.3 mJ at 0.5 kHz and 5 W of output power.…”
Section: Introductionmentioning
confidence: 99%
“…Stolzenburg et al have shown a cavity-dumped thin-disk laser at more than 100 W output power, 300 ns pulse duration at repetition rates up to 100 kHz. 10 Fiber lasers are very capable devices that have advantages on thermal lensing compared to bulk lasers and can produce high power and high pulse energy. 11,12 As Alvarez et al have shown, ns fiber systems can deliver 2.3 mJ at 0.5 kHz and 5 W of output power.…”
Section: Introductionmentioning
confidence: 99%
“…4 laser at 100 kHz by 888 nm diode-laser pumping [5]. In 2007, C. Stolzenburg et al reported a cavity-dumped intracavity-frequencydoubled 515 nm Yb:YAG thin disk laser, and the maximum average output power was 102 W at 50 kHz with a pulse width of 300 ns [6]. Compared with Nd:YVO 4 , Nd:GdVO 4 crystal has better thermal properties.…”
Section: Introductionmentioning
confidence: 99%
“…Composite crystal is another effective way to relieve the thermal lens effect, which can be attributed to the undoped cap of the composite crystal acting as an effective heat diffuser [9]. In this paper, we presented a high repetition rate, high peak power electrooptical cavity-dumping Nd:GdVO 4 laser, using continuousgrown GdVO 4 /Nd:GdVO 4 composite crystal under 879 nm [5] and [6] with dual-end-pumping and thin disk configuration, respectively, we developed a simple and high efficiency V-type cavity with single-end-pumping. The pulse width remained constant at 3.8 ± 0.2 ns, and at repetition rates of 100 kHz, 50 kHz, and 10 kHz, the corresponding peak powers were 34.4 kW, 65.9 kW, and 252.6 kW, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Frequency doubled or tripled solid state lasers based on Nd:YVO 4 and Nd:YAG are very important for material processing in many areas of the micro-electronic and photovoltaic industry. VIS and UV is usually addressed with external [1][2][3][4] or internal [5][6][7][8] frequency conversion. Intra-cavity frequency doubling/tripling is normally preferred due to high conversion efficiency and excellent stability.…”
Section: Introductionmentioning
confidence: 99%